PEMANFAATAN BUKU AKTIFITAS TENTANG PENDIDIKAN SEKSUAL BAGI ANAK USIA DINI DALAM UPAYA MENURUNKAN TINGKAT KEKERASAN SEKSUAL PADA ANAK DI KECAMATAN TAWANG KOTA TASIKMALAYA - Sariestya Rismawati; Siti Saadah Mardiah (LPPM Universitas Bina Bangsa, 2023)
Violence against children is a serious problem and a worldwide issue. Data from KPAI (Indonesian Child Protection Commission), in 2022 there were 834 cases of violence consisting of 400 cases of sexual abuse (47.96%), 395 cases of rape (47.36%), 25 cases of same-sex sexual abuse (2.99%) ) and same-sex rape 14 cases (1.68%). Most sexual violence was at the age of 5-17 years with the highest areas being West Java, DKI Jakarta, East Java, Banten and North Sumatra. In West Java in 2022 the number of sexual violence reached 420 cases and 26 of them occurred in the City of Tasikmalaya. Based on this, it is necessary to provide information to provide an understanding of sexuality with appropriate media and methods for early childhood, one of which is an activity book that contains information about sexuality education. This information can be provided by parents, teachers and health workers. The results of the activity show that there is an increase in early childhood knowledge about sexual education and an increase in the knowledge of teachers and parents regarding the importance of sexual education in early childhood. The conclusion from the activities that have been carried out is that sexual education is important to be given to children from an early age to protect children from sexual violence that might occur